Pink toenails and princess boys: contemporary discourses of boys' gender-fluidity in USA television news. Issue 3 (3rd July 2018) - Zaslow, Emilie
Abstract: This article analyzes four national soft news stories about boys' gender-fluid expression that aired between 2010 and 2012. In each of these stories, boys' feminine-identified actions received explicit support by newscasters and guest experts. Simultaneously, newscaster banter reframed the approbation of gender-fluidity to a more traditional characterization of gender as an immutable binary construct. The acceptance of gender-fluid behavior was attenuated by four discursive frames: the avowal of gender-fluid expression as acceptable only when child's play, the presentation of boys' mothers as supporting the violation of social norms, the positioning of parental acceptance as an act of reluctant resignation, and the assertion of male news reporters' traditional masculinity and heterosexuality. Identifying limits to U.S. news media's support for small acts of gender non-conformity sheds light on journalists' and publics' negotiations of gender and sexuality at a time in which the ontological state of these constructs is being disrupted and rearticulated.